2020
DOI: 10.1111/sum.12623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of subsoil tillage during pipeline construction activities on near‐term soil physical properties and crop yields in the right‐of‐way

Abstract: Natural gas and oil consumption are projected (U.S. Energy Information Administration, 2019) to increase globally and domestically through 2040. According to the report released by the Interstate Natural Gas Association of America (INGAA, 2015), extraction and transportation of natural resources will require establishment of thousands of kilometres of new pipeline infrastructures. As an inevitable consequence, installation of underground pipelines implicates extensive soil disturbance with adverse effects on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
(49 reference statements)
2
14
0
2
Order By: Relevance
“…Larger amounts of non‐decomposed roots in the ROW easement area were explained by high values of soil BD and CI, as reported by Tekeste et al. (2020).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Larger amounts of non‐decomposed roots in the ROW easement area were explained by high values of soil BD and CI, as reported by Tekeste et al. (2020).…”
Section: Resultssupporting
confidence: 78%
“…Dornbush et al (2002) reported that soil disturbance decreased the decay of fine roots due to changes in decomposer dynamics. Larger amounts of non-decomposed roots in the ROW easement area were explained by high values of soil BD and CI, as reported by Tekeste et al (2020).…”
Section: F I G U R Esupporting
confidence: 65%
See 2 more Smart Citations
“…To couple this idea, we need to be able to better explain the mechanisms of yield drag/boost and be able to accurately model them (Kivi et al 2022). For example, one additional known yield drag mechanism in the Accola field is a diagonal line that follows the Bakken Pipeline installation (Tekeste et al 2021); an example of something that we may not currently be able to explain from available yield monitor and remote sensing data alone, and instead need on-field measurements and prior field knowledge to diagnose problems.…”
Section: Discussionmentioning
confidence: 99%